KONSEP EKONOMI ISLAM MENURUT YUSUF QARDHAWI - Syarif Hidayatullah Hakim; Muhammad Yusuf Satria; Rivaldi Saputra; Solahuddin Al-Ayubi (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2025)
This study explores the concept of Islamic economics according to the perspective of Yusuf Al-Qaradhawi, which demonstrates that economics serves as a support for faith in the life of a Muslim. Qaradhawi emphasizes the importance of the concept of istikhlaf in wealth, meaning that humans are merely trustees of Allah's wealth in the world and must use it according to His regulations. The concept of Islamic economics refers to the principles of sharia that guide the Muslim community, so every human activity, including economic policy, development, and economic activities of the community, should refer to Islamic law. In Yusuf Qaradhawi's view, Islam offers a middle path between socialist and capitalist economic systems, avoiding the excesses of both systems by emphasizing balance and justice. Through a literature review and critical analysis of Yusuf Qaradhawi's works, this study reveals the main principles underlying his thoughts on Islamic economics. Some key concepts highlighted include the prohibition of usury (riba), the importance of zakat, and the role of ethics in trade and business. This study also highlights how Yusuf Qaradhawi's thoughts can be applied in the contemporary economic context to offer more ethical and sustainable solutions. Thus, this research provides deep insights into Yusuf Qaradhawi's contributions to the development of Islamic economics and its relevance to current global economic challenges.